Adaptation of cardiac morphology and function to endurance and strength training - Wernstedt, P.; Sjostedt, C.; Ekman, I.; Du, H.; Thuomas, K. A.; Areskog, N. H.; Nylander, E. (Scandinavian Journal of Medicine & Science in Sports, 2002)
Left ventricular (LV) dimensions and function and maximal oxygen uptake (VO2 max) were measured in endurance-trained (10 male, m, 10 female, f), strength-trained athletes (8 m, 10 f) and untrained subjects (9 m, 10 f). LV dimensions were measured using magnetic resonance imaging (MRI) and echocardiography and the results were equal irrespective of method. Endurance-trained m and f had significantly higher LV volumes and mass than both strength-trained and controls. No VO2 max or dimensional differences were seen between strength-trained and untrained subjects. In endurance-trained males, LV volumes and mass/kg bw were higher than in endurance-trained females. There was no significant gender difference for strength-trained or untrained subjects regarding body weight-related heart dimensions. It is concluded that LV dimensions and volumes are strongly dependent on oxygen transport capacity in normal subjects practising different modes of training, and that the gender differences, if LV dimensions are related to aerobic work capacity, are smaller than previously reported.